"Now I always try to stick to the point": Socialization to and from genre knowledge in an English-medium university in Kazakhstan. Issue 48 (November 2020) - Goodman, Bridget A.; Montgomery, D. Philip
Abstract: This paper investigates socialization to genre knowledge in a university in Kazakhstan, a former Soviet republic where the Russian language remains prevalent while Kazakh is still being revitalized and elaborated for academic purposes. The authors conducted a survey of postgraduate students (n = 53) and alumni (n = 57) along with focus groups (n = 26) in a single discipline in order to identify the self-reported extent of genre knowledge development, and processes of development and application, in English, Kazakh, and Russian. Quantitative data show students have slightly higher genre knowledge in Russian than English or Kazakh, but alumni often see English genre knowledge as more important than Russian or Kazakh in their workplaces. Qualitative data show that socialization to English genre knowledge was so successful, at times respondents underwent a process of reverse socialization of practices from English to Russian or Kazakh. In other instances, respondents directly applied skills learned in English to both Kazakh and Russian in ways that suggested they were socializing Russian- and Kazakh-speaking peers to new practices. The results suggest an ecological approach to teaching and learning English for Academic Purposes is recommended to ensure students in multilingual contexts are able to develop and negotiate communication skills among multiple languages.